Galileo and the Inquisition - Carroll, William E. (The journal of religion & society, 1999)
The story of Galileo's encounter with the Inquisition in the early 17th Century continues to be an important part of the story of modernity. Galileo is frequently seen as breaking with the scientific heritage of Aristotle to found a new science of nature and, in the process, he also had to do battle with an entrenched biblical literalism in the Catholic Church. According to the generally accepted view, Galileo's break with both Aristotle and the Inquisition is a founding feature of modern culture. This essay challenges such a view and argues that Galileo's science, at least in its principles, is Aristotelian in inspiration, and that Galileo and the theologians of the Inquisition shared first principles concerning both the complementarity of faith and reason as well as the authority of the Church to be the authentic interpreter of the truths of scripture. In fact, the controversy between Galileo and the Inquisition would be unintelligible were it not the case that all parties shared common first principles.